Psychology and the emotions in the world of literature. Some observations on an example from German sentimentalism - Popov, Ivan (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2023)
The article presents various theories by means of which contemporary literary studies attempt to define the role of psychology in the reception of literature. Although identifying the psychological states of fictional characters obviously plays a key role, a professional reading of a literary work cannot be based on it alone. The second part of the text examines the role that emotions play in the literature of German sentimentalism, as well as the narrative strategies employed by the author Sophie von La Roche in her novel „Geschichte des Fräuleins von Sternheim” in order to achieve the realization of its specific goals.
Keywords: psychology; emotions; literary Darwinism; sentimental literature